The Plan and Realization Evaluation of Supply Crude Oil Activities at PT Kilang Pertamina International - Refinery Unit VI Balongan - Putri, Cheryl Suciyanti; Vikaliana, Resista (Universitas Jember, 2023)
PT Kilang Pertamina International - Refinery Unit VI Balongan is the sixth refinery out of seven refineries owned by PT Pertamina (Persero) that processes crude oil into BBM (Fuel Oil), Non-BBM and Petrochemical products in maintaining energy sustainability in Indonesia. Oil and gas management activities carried out by PT Pertamina must be able to run according to the target. For this reason, in carrying out its business processes, PT Pertamina requires good planning for crude oil. This study focuses on the type of Super Heavy (SH) crude oil including Duri, Cinta, Escalante, Ostra, etc., and Heavy (H) including Banyu Urip, GG Condensate, Minas/SLC, Cabinda, Etame, etc. The purpose of this study is to evaluate the discrepancy between plans and the realization of crude oil orders as well as forecasting for the next 12 periods of crude oil at PT KPI - RU VI Balongan. The results show that several forecasting methods match the demand data pattern, namely the cyclical method, cyclical trend, and multiplicative decomposition (seasonal) methods. In finding the error value forecasting is done by calculating the Mean Absolute Percentage Error (MAPE) method. The selected forecasting method that has the highest accuracy is the cyclical trend forecasting method with a MAPE value of 0.22 for heavy crude oil and 0.13 for super heavy crude oil. The cyclical trend forecasting method has succeeded in reducing the error in the crude supply accuracy level compared to the existing Master Program (MP) crude method.